Diversity of Arthropods in Different Rice Varieties in Bantul Regency - Indah Sri Lestari; Edhi Martono; Arman Wijonarko (Universitas Gadjah Mada, 2020)
High-yielding varieties are used as one of the technologies to increase rice productivity in Indonesia. Varieties, however, invite the arrival of arthropod during their growing phase. One of the method to manage arthropods during the growing stage is the use of high-yielding varieties. In this trial, IR-64, Ciherang, Situ Bagendit, Mekongga and Mixed Varieties were used. The mixed variety is a combination of IR-64, Ciherang, Situ Bagendit and Mekongga. These rice varieties are the most common varieties used by farmers in Bantul Regency. To collect arthropods, the traps used were sweep net, yellow sticky and pitfall traps. The purpose of this study was to determine arthropod’s diversity, evenness and dominance in different rice plant varieties in one planting season. The study was conducted in the village of Wijirejo, Pandak, Bantul, Yogyakarta. The observations were conducted in the evening between 16.00–18.00 p.m., with the interval of twice a week for 5 observations. Arthropods were identified up to the family level. This research resulted in the diversity index (Shannon-Winner) of 1.97–2.82 which is categorized as medium, the evenness index of 0.61–0.71, categorized as medium and the dominance index of 0.10–0.22, categorized as lower level. The ecosystemof the research area was unstable in diversity, evenness, and dominance due to the transition process, and it took quite some times to stabilize the rice fields. Therefore, a more thorough research is still necessary, especially for the ricegrowing season to follow.